Design in a changing world: MacDonald Gill’s large-scale decorative North Atlantic Map in the Queen Mary’s 1st class dining saloon, 1936 - Woodham, Jonathan M (InfoDesign, 2019)
British architect, commercial artist, mural painter, and lettering designer MacDonald Gill (1884-1947) is regarded as one of the leading British graphic designers of the early 20th century but, after a period of comparative neglect, has re-emerged a century later as a major figure in British graphic design history. Well known to many millions of viewers in the earlier decades of the 20th century, his visually sumptuous and striking poster work was widely experienced in Britain through his Wonderground Map of London Town (1914) [Figure 1], an above the surface pictorial map covering the geographical spread of the London Underground system. Other MacDonald Gill work was known all around the world through posters and other publicity for Britain’s Empire Marketing Board (EMB, 1926-1933) and other state organisations; at its height, the British Empire covered about 25% of the world’s land surface. He was also widely commissioned for mural paintings including the imposing large-scale pictorial map of the North Atlantic for the First Class Dining Room of the celebrated Cunard Ocean transatlantic ocean liner, the RMS Queen Mary, whose maiden voyage took place in 1936. It is this large-scale visualisation of the North Atlantic Map of the sea voyage between the two capital cities of London and New York, epitomising what were in essence seen as representative of the old and the new worlds, that provides the major focus of this article.